Analysis of a Hybrid Guided Bomb Control System while Self-guided to a Ground Target - Marta GRZYB (Analiza hybrydowego systemu sterowania bombą kierowaną przy samonaprowadzaniu na cel naziemny, 2022)
This article presents a mathematical model and an algorithm for controlling a guided bomb to a moving and a stationary ground target. The target path was determined from the kinematic relationships of the reciprocal movement of the bomb and the ground target, based on the proportional approximation method. The analysed control system used sliding control, with the PID algorithm to determine the sliding plane. Three types of sliding planes were considered. In addition, a comparative analysis was carried out for three types of controllers: classic PID, sliding and hybrid. Selected results of the computer simulation are listed.
Keywords: System sterowania bombą kierowaną